Resistance mesenteric arteries display hypercontractility in the resolution time of Strongyloides venezuelensis infection - Dela Justina, Vanessa; Gama, Loyane Almeida [UNESP]; Schönholzer, Tatiane; Bressan, Alecsander F.; Lima, Victor Vitorino; Americo, Madileine F. [UNESP]; Giachini, Fernanda R. (Elsevier, 2021)
The blood flow in the mesenteric region is crucial for nutrient absorption and immune response in the gastrointestinal tract. The presence of nematodes or their excreted/secreted products seems to provoke vascular dysfunction. However, it is unclear whether and how the intestinal nematodes with habitat in the intestinal niche could affect the mesenteric vascular resistance. In this study, male Wistar rats were infected with 2000 larvae of S. venezuelensis, and experiments were conducted at 0 (non-infected control), 10 or 30 days post-infection (DPI). Eggs were counted in rats’ feces and adult worms recovered from the small intestine. Second- or third-order mesenteric arteries were extracted for concentration-response curves (CRC) to phenylephrine [PE; in the presence or absence of L-NAME or indomethacin] and acetylcholine. The number of eggs and adult worms were significantly higher in the 10 DPI group than those of 30 DPI group. Augmented PE-induced contraction was seen after 30 DPI compared to 10 DPI or control group. Hypercontractility to PE was partially prevented by L-NAME and wholly abolished by indomethacin incubation. Endothelium-dependent relaxation and endothelial nitric oxide synthase expression were unchanged among groups. COX-1 and COX-2 display a different pattern of expression over the infection. Hypercontractility observed in mesenteric resistance arteries in the resolution time of S. venezuelensis infection may represent systemic damage, which can generate significant cardiovascular and gastrointestinal repercussions.
Keywords: COX; eNOS; Intestinal parasites; Prostaglandins